Dynamics of scrape-off layer filaments in detached conditions. (2nd November 2020) - Schwörer, D.; Walkden, N.R.; Dudson, B.D.; Militello, F.; Leggate, H.; Turner, M.M.
Abstract: The here presented work studies the dynamics of filaments using 3D fluid simulations in the presence of detached background profiles. It was found that evolving the neutrals on the time-scale of the filament did not have a significant impact on the dynamics of the filament. In general a decreasing filament velocity with increasing plasma background density has been observed, with the exception of detachment onset, where a temporarily increase in radial velocity occurs. The decreasing trend with temporary increase was found for filaments around the critical size and larger, while smaller filaments where less affected by detachment. With detachment the critical filament size increased, as larger filaments were faster in detached conditions. This breaks the trend of attached conditions, where the critical size decreases with increasing density.